Maternal and Child Health Situation in South East Asia - Bhandari, Tulsi Ram (Nepal Journal of Obstetrics and Gynaecology, 2013)
Attaining maternal and child health goals remains a challenge to the world. There is need to collect and manage reliable information on maternal and child health for resource generation and proper allocation. This is useful for assessing progress towards the Millennium Development Goals 4 and 5. This paper aims to assess the maternal and child health status in South East Asia Region. Literature search from PubMed, Medline, Lancet, WHO and Google web pages published from 2000 to 2012 was the method adopted for review. All the related references were cited and organized by using referencing software Endnote. Out of the South East Asian countries Thailand, South Korea, Sri-Lanka and Maldives have better maternal child health indicators. South Korea, Sri-Lanka and Maldives follow Thailand in almost indicators. Bangladesh, Bhutan, India, Indonesia, Myanmar, Nepal, and East Timor have poor indicators and are at the bottom of the group. In the South East Asia, there is wide divergence in socio-economic and health status among the countries. More than one-third of maternal and child deaths of global mortality occurs in this region. Many countries in this region are unlikely to achieve the Millennium Development Goals 4 and 5 even if maternal child health is made the priority agenda of all the countries. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 5-10 DOI: http://dx.doi.org/10.3126/njog.v7i1.8825